1996
DOI: 10.1097/00004694-199601000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Distal Tibial Triplane Fractures: Long-Term Follow-up

Abstract: The cases of 35 patients in whom a triplane fracture had been treated at the Ramón y Cajal Hospital were reviewed. The diagnosis of biplane and triplane fracture can now be made by standard radiograph. However, plain radiographs alone did not accurately demonstrate the configuration of the fracture, and computed tomography must be performed. Closed reduction should be attempted first. Failure to obtain or maintain (or both) an adequate closed reduction is an indication for operative treatment. Prognosis is sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
0
32
0
4
Order By: Relevance
“…However, there are many indications that open reduction and internal fixation of deviated fractures greatly reduce the risk of premature closures when compared with conservative therapy 11, 12, 13. Many studies have shown better long-term outcomes in patients treated with anatomical reduction 14, 15, 16…”
Section: Malleolar Fracturesmentioning
confidence: 99%
“…However, there are many indications that open reduction and internal fixation of deviated fractures greatly reduce the risk of premature closures when compared with conservative therapy 11, 12, 13. Many studies have shown better long-term outcomes in patients treated with anatomical reduction 14, 15, 16…”
Section: Malleolar Fracturesmentioning
confidence: 99%
“…Rapariz found the outcome was generally good and that the development of Osteoarthritic changes after 5 years. This was related to the presence of articular incongruity [23]. to cause complications related to growth arrest.…”
Section: What Is the Evidence For Restoring Articular Congruity In A mentioning
confidence: 99%
“…Evidence shows that triplane fractures with <2 mm of weight-bearing articular surface step-off, as seen on a CT scan, are best treated with a closed reduction and percutaneous screws/wires to maintain anatomical reduction whilst immobilized [57]. Recent literature supports open reduction and internal fixation for fractures with >3 mm of initial displacement or >2 mm of residual intra-articular step-off [57][58][59]. We recommend post-reduction CT scan if the surgeon is unsure of the articular reduction, as long-term outcomes are improved with a more accurately reduced articular surface [59,60].…”
Section: Salter Harris Ii: Salter-harris II Distal Tibial Fractures Amentioning
confidence: 99%